Motivation of employees in the public sector of Serbia: A case study - Dragić Milan; Kastratović Edita; Stojković Hadži Strahinja (Trendovi u Poslovanju, 2021)
The paper analyzes the motivational factors and their impact on the behavior and performance of employees in the public sector. The survey of public sector employees was conducted on the territory of Banat. The collected data were subjected to a descriptive and comparative statistical procedure. The results of the research showed that there is a certain deviation in terms of employees' attitudes about motivational factors. The results confirmed the specificity and at the same time the difference in terms of the attitudes of public sector employees in the territory of Banat in relation to the region and the world.